2011
DOI: 10.1364/ao.50.002383
|View full text |Cite
|
Sign up to set email alerts
|

Maskless fabrication of three-dimensional microstructures with high isotropic resolution: practical and theoretical considerations

Abstract: A maskless three-dimensional (3D) microfabrication method based on a digital micromirror device (DMD) is proposed for high lateral and vertical resolution. A substrate is scanned laterally under virtual masks of the DMD. The masks are allocated to a large number of virtual slices, all of which are projected in a single scan of the stage. A theoretical model for the cumulative dose distribution in a photoresist is derived and used to predict the resulting 3D profile. Experiments showed that the proposed method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Due to the properties of the photoresist, the relationship between the exposure depth and the exposure dose is nonlinear, also. Some studies [ 28 , 29 ] have reported that the exposure depth is a logarithmic function of the dose and can be determined by the contrast curve, which is defined as the linear slope of the contrast curve as follows: …”
Section: Experiments Setup and Methodsmentioning
confidence: 99%
“…Due to the properties of the photoresist, the relationship between the exposure depth and the exposure dose is nonlinear, also. Some studies [ 28 , 29 ] have reported that the exposure depth is a logarithmic function of the dose and can be determined by the contrast curve, which is defined as the linear slope of the contrast curve as follows: …”
Section: Experiments Setup and Methodsmentioning
confidence: 99%
“…The digital lithography system could transfer customer design to digital signals, and make the digital mirror devices (DMD) array works like a mask to write patterns directly onto photoresist on substrates [1][2][3][4][5], which has great advantages in terms of mask-free for cost saving, improvement of production rates, and allows for rapid changes of the pattern on both rigid and flexible substrates, etc. [6][7].…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…Generally, the maskless lithography technique fabricates a 3D microstructure by the multilayer slicing approach to obtain the approximately continuous profile. Slicing strategies such as equal‐height scan applied in the 3D printing region and equal‐exposure‐dose scan strategy [13, 14] have been developed. However, the profile precision is mainly guaranteed by a large number of slicing layers and the efficiency of fabrication is limited.…”
Section: Introductionmentioning
confidence: 99%